Increased Wage Inequality via ICTs: Making a Case for Human Capital Investment - Loh, Yvonne Ai-Chi (2017)
Globalisation and technological advances have affected workers' livelihoods. This study analysed how capital investment in ICTs at the workplace affected marginalised low wage workers in a large sample of firms (n=632) in Singapore. We found that social investment by the state for ICTs investments in workplaces led to a significant negative, albeit marginal, reduction in wage growth. We argue that these findings are supported by economic theory, and propose that government investment balance towards higher-order digital skills. We advocate for further research to measure the impact of worker ownership in enterprises on productivity growth, and hence equality objectives.